Female perineal injuries in children and adolescents presenting to a paediatric emergency department. Issue 1 (9th March 2015) - Roland, Damian; Lewis, Gareth; Rowlands, Rachel; Davidson, Emmanuel; Davies, Ffion
Abstract : This retrospective case series determined documentation quality and likelihood of safeguarding issues in girls  aged 0–15 years with perineal and genital injuries presenting to a paediatric emergency department (ED). During the period between 2002 and 2010, cases were identified and clinical information was recorded. Cases were cross-referenced against the hospital's safeguarding unit's records up to 2011. In total, 181 case notes were available for review with 76.2% of patients discharged home from the ED. Fewer than 50% of case notes contained clear anatomical description of the injuries. In 51 (28.2%) cases, child safeguarding issues were considered, with specific referrals made to safeguarding services in 20 of these (11.0%). Only one case involved subsequent child safeguarding proceedings. Clear documentation of injury patterns by medical staff was poor, but medical and nursing staff should not be anxious about dealing with this cohort of patients as they are no different from other incidental injuries needing diligent levels of child safeguarding awareness.